Low-frequency Magnetic Field Emission and Limited Value Inside EMUs - WANG Yi-min; YU Ding-hua; CAI Wan-yin (机车电传动)
Based on the synthesized analysis of correlative standards and measurement data, requirement of low-frequency magnetic field limited value for EMUs was put forward, which is advantageous for drafting railway specification of electromagnetic radiation protection inside EMUs.